An analysis of gas accidents in Chinese coal mines, 2009 – 2019. (March 2022) - Li, Kaizhi; Wang, Liguo; Chen, Xiangjun
Highlights: The frequency of major gas accidents with three or more deaths between the years 2009–2019 was reviewed. We analyzed the characteristics and rules of the accident in time and space. We analyzed the cause of the accident by using an appropriate model. Then suggestions for accident prevention were discussed from three aspects: safety technical measures, safety management and safety culture. Abstract: Underground coal mining has long been a dangerous occupation, particularly in China, where the incidence of gas-related accidents is high. This paper analyzes the frequency and the temporal and spatial distribution of major gas accidents in China that resulted in three or more deaths during the period 2009–2019. The analysis reveals a downward trend between 2009 and 2014, followed by relative stability from 2015 to 2019. The number of gas-related accidents was higher in some months than others, and most accidents occurred between 9 a.m. and 12 noon. There is also a clear geographical distribution pattern, with the majority of accidents occurring in provinces in the southwest region of China. While the immediate cause of these accidents is unsafe conditions or unsafe behavior, the study finds that the root cause is the lack of a safety culture. The article ends by making some suggestions for accident prevention, under the categories of technical measures, safety management, and safety culture.